2005
DOI: 10.7205/milmed.170.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Malaria on a Military Peacekeeping Operation: A Case Study with No Cases

Abstract: The chain of command can have a significant impact on compliance with malaria protection measures, which might reduce incidence of the disease in the deployed population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In such conditions, the soldiers were probably more closely supervised by the command, so they were submitted to a higher pressure to comply with the chemoprophylaxis. Indeed, the good health of the soldiers, including the prevention of malaria, was an important concern of the command because of the operational nature of the mission: the global health of the group had to be preserved for a military purpose [46]. Compliance with malaria chemoprophylaxis was also better among civilian travellers who were taking part in an organized trip compared to those traveling independently [35].…”
Section: Discussionmentioning
confidence: 99%
“…In such conditions, the soldiers were probably more closely supervised by the command, so they were submitted to a higher pressure to comply with the chemoprophylaxis. Indeed, the good health of the soldiers, including the prevention of malaria, was an important concern of the command because of the operational nature of the mission: the global health of the group had to be preserved for a military purpose [46]. Compliance with malaria chemoprophylaxis was also better among civilian travellers who were taking part in an organized trip compared to those traveling independently [35].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a preventive approach is curtailing the introduction of resistant malaria to drug sensitive regions 23 . A British study done in 2015 on 512 soldiers stationed at a high risk area, reported that no cases develop if the chain of command is proactive about the implementation of malaria prevention policies 24 .…”
Section: Discussionmentioning
confidence: 99%
“…They have also trialled text messaging to successfully confirm the daily ingestion of malaria chemoprophylaxis in a deployed setting 14. Many of these measures have been effectively implemented by the UK Armed Forces in the past15 and when these standards have slipped malarial outbreaks have occurred 16 17. In the case of this patient, as a civilian healthcare worker for an NGO, none of these measures were used, aside from the use of mosquito nets.…”
Section: Discussionmentioning
confidence: 99%